(untitled) (Plant Tissue Culture and Biotechnology, 2017)
A plant regeneration system was established from hypocotyl explants of in vitro grown seedlings of A. officinalis and in vitro proliferated shoots, respectively through somatic embryogenesis and embryogenic calli. Somatic embryogenesis was significantly influenced by the types of plant growth regulators. Embryogenic calli with somatic embryos developed well in MS supplemented with 2.0 ‐ 4.0 μM BAP and 1.0 ‐ 4.0 μM 22,4‐D, NAA or IBA. The highest frequency (95.3%) of embryogenic calli and 55.2 somatic embryos formation were obtained when the MS was amended with 4.0 μM BAP and 2.0 μM 2,4‐D. The best embryo germination occurred in 1.0 μM BAP supplemented MMS. The highest 97.2% of shoot proliferation was observed in embryogenic calli in MS medium containing 2.0 μM BAP and 1.0 μM IBA. In vitro grown shoots were rooted in MMS with 1.0 ‐ 2.0 μM IBA. Regenerants were transferred to vermicompost and successfully established under an ex vitro environment in garden soil with 80% survival rate. Plant Tissue Cult. & Biotech. 27(1): 21-31, 2017 (June)